Endovascular Treatment of Ruptured Abdominal Aortic Aneurysms with Hostile Aortic Neck Anatomy. Issue 3 (September 2015) - Broos, P.P.H.L.; 't Mannetje, Y.W.; Cuypers, Ph.W.M.; van Sambeek, M.R.H.M.; Teijink, J.A.W.
Abstract : Objective: To compare the mid-term results of endovascular aortic aneurysm repair (EVAR) for ruptured abdominal aortic aneurysms (RAAAs) in patients with favourable aortic neck anatomy (FNA) and hostile aortic neck anatomy (HNA). Methods: Patients treated for a RAAA in a high volume endovascular centre in the Netherlands between February 2009 and January 2014 were identified retrospectively and divided into two groups based on aortic neck anatomy, FNA and HNA. HNA was defined as RAAA with a proximal neck of <10 mm, or a proximal neck of 10–15 mm with a suprarenal angulation (α) >45° and/or an infrarenal angulation (β) >60°, or a proximal neck of >15 mm combined with α >60° and/or β >75°. Patient demographics, procedure details, 30 day and 1 year outcomes were recorded. Results: Of 39 included patients, 17 (44%) had HNA. Technical success was 100% for FNA and 88% for HNA ( p  = .184). There were no type IA endoleaks on completion angiography in either group; however, more adjunctive procedures were necessary for intra-operative type IA endoleaks in the HNA group (24% vs. 0%, p  = .029). Thirty day mortality rates were comparable, FNA 14% vs. HNA 12% ( p  = 1.000). There were no statistically significant differences at 1 year follow up in type I endoleaks, secondary endovascular procedures, or all cause mortality. Conclusion: Emergency EVAR provides excellent results for treatment of RAAA patients with both FNA and HNA. EVAR in RAAAs with HNA is technically feasible and safe in experienced endovascular centres. Article history: